(untitled) (Research, Society and Development, 2021)
Breast cancer is an important public health problem. Primary prevention seeks to reduce exposure to risk factors and encourages lifestyle changes. This study aims to assess knowledge and sources of information about risk factors for breast cancer among women at a secondary care center in Belo Horizonte, Brazil. This is a cross-sectional study, whose data collection was performed using a semi-structured questionnaire that included demographic variables (such as age, education, marital status and occupation) and research on information sources, access to information, risk factors and causes of breast cancer. A total of 398 women were included, aged between 35 and 69 years. The main source of information about Breast Cancer was the media, followed by the primary care unit. 79.6% of women have never participated in Pink October activities. Twelve items were listed as possible risk factors for breast cancer, and seven of those were modifiable risk factors. The average number of correct items identified was 1.38 and 1.76, respectively. The most recognized risk factor was family history of breast cancer. Genetics was described as the main cause of the disease. Our data show the limited awareness, as well as the reduced scope of public health actions towards breast cancer health promotion. It demonstrates the urge for reformulation of the breast cancer awareness information until it reaches the target audience. In addition, it is crutial that women assume their individual health responsibility, adopting a better lifestyle.